STRATEGY FOR THE FORMATION OF OPTIMAL CAPITAL STRUCTURE WITH SWOT ANALYSIS IN PHARMACEUTICAL SUBSECTORS COMPANIES - Andini Nurwulandari; Hasanudin Hasanudin; Burhan Artardo (UNIVERSITAS INDRAPRASTA PGRI, 2021)
This study aims to determine the optimal capital structure formation in pharmaceutical sub-sector companies during the period 2014 - 2019 by analyzing profitability, dividend policy, and the SWOT matrix model by analyzing strengths, weaknesses, opportunities, and threats and being the basis for formulating various alternatives. These strategies can be carried out by company management. The company's profitability is not optimal; the company can still distribute dividends. And the results of the study illustrate that the capital structure of the pharmaceutical sub-sector company is not yet optimal. The average proportion of long-term debt capital structure of pharmaceutical sub-sector companies is 18.43% debt and 81.57% equity. Calculation of company value from 2014 - 2019 using the Modigliani Miller approach with a debt proportion of 0% - 100% shows that the highest company value of pharmaceutical sub-sector companies is in the composition of 30% debt and 70% equity. The total WACC averages 47% of the debt. By producing a WACC of 1.92% - 16.89% with a total average WACC of 10%. By considering the WACC, it is concluded that the optimal capital structure for the average pharmaceutical sub-sector company is in the composition of 30% to 60% of the debt. Meanwhile, the average WACC is 11.10%, and with financial distress, the average WACC value is 10%. Based on considering the company value and WACC above, the capital structure of the pharmaceutical sub-sector company is not optimal. The optimal capital structure will result in high Firm Value and the lowest cost of capital. The results of this study have implications for financial performance, capital structure, firm value, the weighted average cost of capital (WACC), and SWOT analysis, which need to be optimized to achieve optimal capital structure.